PENGARUH ALOKASI DANA ZAKAT TERHADAP KINERJA KEUANGAN PERBANKAN SYARIAH - ,, Amirah; Raharjo, Teguh Budi (PERMANA, 2014)
The purpose of this research is to examine the effect of the allocation of zakat funds on the financial performance of Islamic banking 2009-2012. The choosing of the samples done by purposive sampling with the requirement all the companies publishing their sources and uses of funds statement of zakat, in order to obtain four banks, namely Bank Syariah Mandiri, Bank Muamalat, BRI syariah, and Bank Mega Syariah. Testing conducted using Partial Least Squares ( PLS ) mediation effect, ie entering Dana Pihak Ketiga as an intervening variable. Results of this study indicate that the zakat significant effect on the financial performance of Islamic banking to Dana Pihak Ketiga as mediating variable. These results indicate that Islamic banks have implemented effective marketing strategies through distribution of zakat is performed simultaneously in the framework of Corporate Social Responsibility (CSR) in attracting investors to invest their funds in Islamic banks.Keywords : zakat , dana pihak ketiga , islamic banking financial performance, corporate socialresponsibility (CSR)